PERAN SERTA DAN KESADARAN MASYARAKAT DALAM PENGELOLAAN SAMPAH DI DISTRIK (KECAMATAN) NABIRE - Febhy Mardianthy Gybriella Erari; Mohammad Mirwan (EnviroUS, 2021)
As a city center and economy with a view of piles of rubbish, rubbish scattered on the side of the road, garbage dumped in rivers, garbage that destroys green lines are common things. Public concern and awareness of the bad effects of waste for the future. The household waste in Nabire District is the biggest problem for the environment in the Nabire District. The purpose of this research is to reduce the amount of waste generation in Nabire District and to know the squeeze and the community of the waste generated in Nabire District. The method used in the study of normality analysis and correlation method. From the results obtained, Nabire District produces an average of 45,625 kg / 16 days of waste with a composition of 94 kg / 16 days of organic waste, 202 kg / 16 days of inorganic waste. The conclusion of this research is that there is a reduction in waste generation with the participation of the community from the initial total waste of 730 kg / day to 434 kg / day.